The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1972
DOI: 10.1071/ar9720913
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of meat meals for poultry. VII.* Effect of processing temperature on total and biologically available amino acids

Abstract: The effect on the protein quality of meat meals of processing them under commercial conditions in a continuous dry renderer at maximum temperatures ranging from 116 to 160°C for a running time of 115 min was studied. Although the total levels of amino acids were little affected by processing temperatures, the biological availability of all essential amino acids, as determined by the protozoan Tetrahymena pyriformis, was reduced as the processing temperature increased. At 140 and 160°C the availability of certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Average total essential and non-essential amino acids content of processed samples (34.6% and 52.7% CP) was similar to that found by Hendriks et al (2002) in 94 MBM samples (36.2% and 60.7% CP). In addition, the concentrations of essential and non-essential amino acids agree with the Degussa database (AminoDataÒ 3.0; Evonik Degussa GmbH, Hanau-Wolfgang, Germany) of 377 MBM samples and are similar to the ranges reported in the literature (Kondos and McClymont, 1972;Hendriks et al, 2002).…”
Section: Protein Qualitysupporting
confidence: 86%
See 3 more Smart Citations
“…Average total essential and non-essential amino acids content of processed samples (34.6% and 52.7% CP) was similar to that found by Hendriks et al (2002) in 94 MBM samples (36.2% and 60.7% CP). In addition, the concentrations of essential and non-essential amino acids agree with the Degussa database (AminoDataÒ 3.0; Evonik Degussa GmbH, Hanau-Wolfgang, Germany) of 377 MBM samples and are similar to the ranges reported in the literature (Kondos and McClymont, 1972;Hendriks et al, 2002).…”
Section: Protein Qualitysupporting
confidence: 86%
“…Previous works have shown that when proteins are processed with heat or pressurized steam, amino acids may be destroyed and/or altered and thus become unavailable to animals′ metabolism (Kondos and McClymont, 1972; Wang and Parsons, 1998). Although, the exact mechanisms by which heat and pressure affect amino acids concentration are unknown, the reason may be associated with racemization or cross‐linking of amino acids (Singh, 1991; Shirley and Parsons, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, processing temperature has been shown to greatly affect digestibility of AA in animal meals. Kondos and McClymont (1972) reported that the availability of the essential AA in MBM decreased markedly when the processing temperature was increased from 116 to 160°C. In addition, Batterham et al (1986) found that lysine availability in MBM for chicks decreased from 85 to 35% when the processing temperature increased from 125 to 150°C.…”
Section: Introductionmentioning
confidence: 99%